2010
DOI: 10.1093/brain/awq146
|View full text |Cite
|
Sign up to set email alerts
|

A serial study of retinal changes following optic neuritis with sample size estimates for acute neuroprotection trials

Abstract: Following an episode of optic neuritis, thinning of the retinal nerve fibre layer, which indicates axonal loss, is observed using optical coherence tomography. The longitudinal course of the retinal changes has not been well characterized. We performed a serial optical coherence tomography study in patients presenting with optic neuritis in order to define the temporal evolution of retinal nerve fibre layer changes and to estimate sample sizes for proof-of-concept trials of neuroprotection using retinal nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 39 publications
3
118
1
3
Order By: Relevance
“…Macular volume is also lost in eyes affected with ON when compared with disease-free control eyes. 14 Significant RNFL thinning was found after ON in a study by Henderson et al, 106 evident within 3 months with 99% of the total loss occurring within 5 months of the episode of ON. Eyes with greater RNFL loss had a worse visual prognosis at 3 months.…”
Section: Ms With Onmentioning
confidence: 96%
“…Macular volume is also lost in eyes affected with ON when compared with disease-free control eyes. 14 Significant RNFL thinning was found after ON in a study by Henderson et al, 106 evident within 3 months with 99% of the total loss occurring within 5 months of the episode of ON. Eyes with greater RNFL loss had a worse visual prognosis at 3 months.…”
Section: Ms With Onmentioning
confidence: 96%
“…The fact that the thickness of the peripapillar and macular retinal nerve fiber layer (pRNFL and mRNFL) and ganglion cell layer combined with the inner plexiform layer (GCIP) were reduced in the affected eye after 6 months, confirms that these cells are the primary cellular site of the disease (Al‐Louzi et al., 2015; Gabilondo et al., 2015; Henderson et al., 2010). The GCIP layer was the preferred outcome measure over the pRNFL and mRFNL, since the GCIP layer is unaffected by optic disc edema and therefore provides more precise information on the structural retinal changes caused by ON (Syc et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with severe ON, an inverse relationship between pRNFL thickness (i.e., optic disc edema) and visual acuity was observed for nontreated patients, which is in agreement with previous findings (Beck et al., 1992; Henderson et al., 2010; Malik et al., 2014). The possible mechanism for the steroid treatment effect may involve a suppression of the inflammation associated with acute ON, which in turn may limit the neuronal damage and accelerate visual function recovery (Beck et al., 1992; Kapoor et al., 1998; Sellebjerg, Nielsen, Frederiksen, & Olesen, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous studies have reported the timing of pRNFL and GCIPL thinning after the onset of ON. 14,19 Henderson et al 19 showed that RNFL thinning can be observed during the first 6 months following ON and that 490% of this fiber loss occurred by the end of the third month. Another study reported that RNFL thinning occurred gradually, up to 6-9 months after ON, and that GCL thinning occurred earlier than RNFL thinning, within a few weeks after acute ON.…”
Section: Discussionmentioning
confidence: 99%